UMP exploring possible collaboration with Proton - Laili, Zulkepeli (Penerbit UMP, 2015)
Selangor, June 9, 2015- Universiti Malaysia Pahang (UMP) Vice Chancellor Prof. Data' Dr. Daing Nasir Ibrahim led a group of senior faculty members consisting of faculty deans to a visit to Proton Centre of Excellence here recently.